Diagnosis and Management of Spontaneous Lumbar Venous Retroperitoneal Hematoma in Setting of Deep Venous Thrombosis: A Case Report and Algorithm - Joseph Tseng; Michael Leshen; Todd Chapman; Ryan Scott; Olga Kalinkin (Case Reports in Radiology)
Retroperitoneal hematoma is rare and benefits from a systematic approach to prevent morbidity and mortality. Management of such bleeds is based upon patient stability, the cause (spontaneous or posttraumatic), and source (arterial or venous). Herein, the authors describe a diagnostic and management algorithm for retroperitoneal hemorrhage with an example of a rare lumbar venous bleed under the complicated clinical setting of deep venous thrombosis.